POLARIZABILITY AND NUCLEAR SHIELDING FOR THE SODIUM ANION IN CONDENSED PHASES - Pyper, N; Pike, C; Edwards, P (1993)
The environmental modifications of the polarizability, the diamagnetic contribution to the susceptibility, and the nuclear shielding of the sodium anion (Na-) in the cryptand salt Na-·Na-C222 (C222 = cryptand 222) are deduced from ab-initio quantum chemistry computations. The point charge electrostatic contribution to the anion environment in the cryptand reduces to 643 au, the free anion polarizability of 1090 au predicted taking account of electron correlation using the coupled electron pair approximation. This polarizability is found to be further diminished to around 400 au on introducing a realistic model of the full environment in the cryptand. The electron correlation contribution to the polarizability is largely suppressed on entering the condensed phase. The diamagnetic contribution to the susceptibility is found to be reduced in magnitude by 32% on introducing a model for the full environment in the cryptand. This result, combined with an average energy approximation analysis of the ab-initio polarizabilities, shows that environmental modifications of the ground-state wave functions are responsible for about one-third of the polarizability reductions, with two-thirds arising from environmental modifications of the excited states and their excitation energies. The contribution of the two 3s electrons to the diamagnetic part of the nuclear shielding is found to be enhanced by 9% when the free anion experiences the present model for the environment in the cryptand, the core contribution remaining essentially unchanged. The nucleus in the cryptated anion is predicted to be shielded by 3.58 ppm relative to that in an isolated gaseous sodium atom, compared with the 2.88 ppm nuclear shielding in the free anion relative to that in the free atom. This comparative insensitivity of the shielding is consistent with the experimental observation that the Na- shielding (uncorrected for bulk susceptibility) almost always lies within ±1 ppm of a 1.5 ppm shielding relative to the free sodium atom. This explains how the nuclear shielding can be so comparatively environment insensitive in a species interacting sufficiently strongly with its surroundings as to experience a reduction in polarizability by a factor of 2.7.